Pork extract for manufacturing capsulated medicines: Istiḥālah in the light of Maqāsid Shari‘ah - Busari, Saheed Abdullahi; Husni, Ahmad Muhammad (2021)
Bringing benefits and repelling harm is one of the main objectives embedded in the divine law of Shariah. The law of Shariah came in its entirety for the preservation of fundamental principles of Allah on the creation such as the five maqāsid al-shari‘ah principles. Since the dawn of the scientific revolution, genetic engineering has triggered several debates at different levels among the stakeholders. Clearly, there are opinions between the process of transformation and mere transmutation of the substance, some of which are subject to consensus and some differs. This study aims to analyze the juristic implication of the permissibility of using gelatin extracted from pig parts in the pharmaceutical industry. The study adopted the inductive approach to collect the information recorded in contemporary literature in this regard and then followed by a comparative analytical study to highlight the agreed and disagreed facts between Shariah sources and other sciences. The most important note is that in the event of a choice, consuming foods and drinks containing pork gelatin is not permissible. By the same analogy, the capsulated medicines cannot be taken, and this study is purely for the case when it is necessary and there is no alternative.